Alfonso V el Magnánimo y el Siti Perillós (1422-1458). - CAPILLA ALEDÓN, GEMA BELIA (Scripta, 2017)
Alfonsus V the Magnanimous, King of Aragon (1416-1458), is an exceptional case to the political power representation, because he is the first european king in making an image speech of himself in which coexists and combines the values and the ways of medieval representation with the moderns sponsored by the Italian Humanism. One of the most controversial and interesting elements inside his image speech are his royal emblems, medieval tradition elements that, precisely, not only remain but even gather steam in the advance at the use of the classical forms. One of this emblems is exactly which that has a closer relationship with the medieval tradition: the siege perilleous of the Saint Graal. The aim of this article is to analyze the use of this emblem made by the king and offer the reconstruction of its history like an specific evidence of his representative speech.